Optimalisasi Daya Tarik Wisata Alam sebagai Pendukung Pengembangan Desa Wisata Duda Timur, Karangasem, Bali - Putu Guntur Pramana Putra; Ni Wayan Mekarini; Ida Ayu Anggreni Suryaningsih (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2023)
Natural tourist attraction is a tourist attraction in the form of diversity and uniqueness of natural wealth which includes natural tourist attractions based on the potential diversity and uniqueness of the natural environment that exists in the sea and land. Duda Timur is one of the villages that has a variety of natural potential that can be developed, namely in the natural attractions of land areas in the form of plantations, hills and rivers, the purpose of this study is to identify the potential possessed by the village that can be developed as a nature-based tourist attraction. The data collection techniques used in this research are observation, in-depth interviews and literature studies. The data analysis used was descriptive qualitative. The result of this research is that Duda Timur Village has tourism potential that can be developed, namely Jagasatru Waterfall, Beji Dedari and Bukit Putung